2013
DOI: 10.1111/jir.12049
|View full text |Cite
|
Sign up to set email alerts
|

Associations of symptoms of anxiety and depression with diabetes and cardiovascular risk factors in older people with intellectual disability

Abstract: Increased anxiety symptoms and diabetes are related in older people with ID. This association may be bidirectional. No other associations of depression and anxiety symptoms with cardiovascular risk factors could be proven to be significant. Therefore, more research is needed to unravel the mechanisms of stress, mood disorders and cardiovascular disease in older people with ID. To provide comprehensive care for older people with ID, screening for diabetes and components of the metabolic syndrome in people with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…The prevalence estimates ranged from 2% 84 to 13%. 90 The pooled prevalence of T2DM was 7.6%. The prevalence of any diabetes was 8.7%; this ranged from 2% 84 to 11% 95,102,117 (data not presented).…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence estimates ranged from 2% 84 to 13%. 90 The pooled prevalence of T2DM was 7.6%. The prevalence of any diabetes was 8.7%; this ranged from 2% 84 to 11% 95,102,117 (data not presented).…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…90 Combined evidence from other studies, as presented in the meta-analysis in Chapter 2, suggests a prevalence rate of 8% for T2DM in adults with ID. Data to enable comparison of rates for T2DM in the UK population with ID are scarce (it is suggested that 85-90% of diabetes is T2DM 20 ).…”
Section: Comparison With Previous Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…de Winter, Echteld, and Evenhuis (2014) studied chronic kidney disease, and found that overall rates were equal to the general population (i.e., 15.3%). They also reported that kidney disease was significantly associated with age, as well as with Down syndrome, obesity, hypercholesterolemia, and hypothyroidism.…”
Section: Ha-id In the Netherlandsmentioning
confidence: 98%
“…In their review, Haveman et al (2010) noted the complete lack of articles focused on co/multimorbidity, which is surprising given that co/multimorbidity is known to be high among adults with intellectual and developmental disabilities and to increase with age. Since then, discussions of comorbidity (e.g., mental health and Health Surveillance in Older Adults cardiovascular diseasedsee de Winter, Hermans, Evenhuis, & Echteld, 2015) and multimorbidity (see have appeared in the literature.…”
Section: Aging and Healthmentioning
confidence: 99%